LÍMITES CONSTITUCIONALES AL IUS CONTRAHENDI INTERNACIONAL DEL ESTADO CUBANO - Caballero, Yoel Moré (Universidad de Costa Rica, 2022)
The present article realizes a study of the formal and material conditionings thatthe Cuban Constitution imposes with regard to the celebration of internationalagreements. With this intent the established limits are examined for the conclusionof all kinds of agreements on the part of the Cuban State valuing the reasons ofthe existence and application of such conditionings, as well as the effects thatthey generate and its relative correspondence with the principles internationallyrecognized by the Law of Treaties. The point of item is historical but the essentialinterest is to concentrate on the system of the current in force Constitution from 1976by means of the analysis of content of its procedure that its interpretation allows inrelation with the context of the juridical disposition and its social specific context.